2021
DOI: 10.1002/aenm.202100881
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectionally Compatible Buffering Layer Enables Highly Stable and Conductive Interface for 4.5 V Sulfide‐Based All‐Solid‐State Lithium Batteries

Abstract: High‐voltage all‐solid‐state lithium batteries (HVASSLBs) are considered attractive systems for portable electronics and electric vehicles, due to their theoretically high energy density and safety. However, realization of HVASSLBs with sulfide solid electrolytes (SEs) is hindered by their limited electrochemical stability, resulting in sluggish interphase dynamics. Here, a bidirectionally compatible buffering layer design scheme is proposed to overcome the interfacial challenges of sulfide‐based HVASSLBs. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 47 publications
2
51
0
1
Order By: Relevance
“…In coating materials for high voltage active materials, even though the oxidation voltage of coating materials (Li 2 CO 3 , [ 68 ] Li 3 BO 3 , [ 68 ] LiNbO 3 , [ 20 ] Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , [ 69 ] Li 2 ZrO 3 , [ 20 ] and LiZr 2 (PO 4 ) 3 [ 70 ] ) is lower than the cut off voltage of ASSBs with high voltage active materials, the coating materials have significantly decreased the interfacial resistance. [ 71–75 ] Therefore, those coating materials would be also oxidized on the high voltage active materials but they still work as the Li ion conductive material. Based on the study about coating materials for high voltage electrode and the obtained Nyquist plots (Figure 3b), we speculate that the oxidation of LiI was limited and the interface area between Li 2 S and LiI would be maintained (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…In coating materials for high voltage active materials, even though the oxidation voltage of coating materials (Li 2 CO 3 , [ 68 ] Li 3 BO 3 , [ 68 ] LiNbO 3 , [ 20 ] Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , [ 69 ] Li 2 ZrO 3 , [ 20 ] and LiZr 2 (PO 4 ) 3 [ 70 ] ) is lower than the cut off voltage of ASSBs with high voltage active materials, the coating materials have significantly decreased the interfacial resistance. [ 71–75 ] Therefore, those coating materials would be also oxidized on the high voltage active materials but they still work as the Li ion conductive material. Based on the study about coating materials for high voltage electrode and the obtained Nyquist plots (Figure 3b), we speculate that the oxidation of LiI was limited and the interface area between Li 2 S and LiI would be maintained (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is one thing in common for all cathode materials that no electrode can escape the effect of surface/interface structure evolution at the atomic scale during battery cycling. In SSBs, it has been reported that many transition metals (TMs) at a high oxidation state have been found to be unstable against SEs [61][62][63]. The instability of surface phase and side reactions at CAM-SE interface could cause severe structure evolution, resulting in fast capacity fading.…”
Section: Surface/interface Structure Evolution At the Atomic Scalementioning
confidence: 99%
“…, Li 2 WO 4 –LCO/Li 6 PS 5 Cl, LiZr 2 (PO 4 ) 3 –LCO/Li 6 PS 5 Cl, LiNbO 3 –NCM811/Li 10 SnP 2 S 12 , etc. , 32–34 but most are limited to less than 180 mA h g −1 due to the material's own capacity limitation. Therefore, it is appealing to apply high-capacity lithium-rich cathode materials in ASSLBs to improve their practical energy density.…”
Section: Introductionmentioning
confidence: 99%